Preparation of monophasic titanium sub-oxides of Magnéli phase with enhanced thermoelectric performance. Issue 2 (February 2018) - Fan, Yuchi; Feng, Xiaopeng; Zhou, Weiwei; Murakami, Shou; Kikuchi, Keiko; Nomura, Naoyuki; Wang, Lianjun; Jiang, Wan; Kawasaki, Akira
Abstract: Titanium sub-oxides of Magnéli phase are considered as earth-abundant, non-toxic materials for thermoelectric application at high temperature, but very limited investigation has been reported mainly owing to the difficulty lying in obtaining monophasic material. Herein we describe a facile strategy to prepare monophasic Ti9 O17 and Ti4 O7 powder, in which the single Ti9 O17 phase is obtained for the first time. After spark plasma sintering, the thermoelectric properties of monophasic Ti9 O17 and Ti4 O7 ceramics are studied comparatively. Despite the one magnitude lower electrical conductivity, Ti9 O17 shows higher power factor compared with Ti4 O7 due to the large Seebeck coefficient. Moreover, with the low electronic thermal conductivity, sub-micron scaled grain size and nano-scaled crystallographic shear plane, the Ti9 O17 ceramic exhibits even lower thermal conductivity compared to Ti4 O7, leading to a ZT of 0.16 at 764 K, which is the best thermoelectric performance among reported Magnéli phases.